COMPARISON OF LANGUAGE STYLES IN NOVEL ATHEIST BY ACHDIAT KARTA MIHARDJA AND NOVEL TELEGRAM BY PUTU WIJAYA - Aryana, Andi; Darwis, Muhammad; Nurhayati, Nurhayati (Universitas Hasanuddin, 2018)
This study discusses the comparison of language style in novel Atheist by Achdiat Karta Miharja and novel Telegram by Putu Wijaya. The aims of this study are (1) to describe the embodiment of language styles in novels Atheist and novels Telegram, and (2) to describe the comparison of language styles in novels Atheist and novels Telegram. This research is a qualitative research usingdescriptive method. The approach used in this research is stylistic approach. Sources of data in this study is a text that contains the style of rhetorical language and figurative style of language. The results show that: (1) the style of language used in the novel Atheist is the style of language; Hyperbole, simile, metaphor, personification, antonomasia, and sarcasm. The style of language found in the novel Telegram namely; Hyperbole, simile, metaphor, personification, antonomasia, and metonimia. Based on the language style found, there are three types of word classes used as word choice in realizing the style of figurative language and style of rhetorical language, namely; Nouns,verbs, and adjectives. (2) The similarity between novels Atheist and novels Telegram is the similarity of hyperbola-style, personification, and antonomasia-forming structures. The difference between the novel Atheist and the novel Telegram lies in the metaphorical style marker which in the novel Atheistis a transitive verb, while in the novel Telegram is a concrete noun.